Screens that educate: music series to grow up with rhythm and art - López García, Narciso José; Sánchez Parra, María José (Journal of Learning Styles, 2026)
This study focuses on animated series with an artistic-musical approach as educational resources that combine entertainment and learning while stimulating students’ sensory, cognitive, and emotional development. Through the analysis of three representative series (Little Einsteins, Do, Re, Mi, and De aquí para allá) their potential to foster musical appreciation, active listening, sense of rhythm, and aesthetic sensitivity from early educational stages is examined. These productions not only enrich children’s cultural experience but also strengthen essential competencies in Arts Education, promoting creativity, collaboration, and enjoyment of art. Additionally, this study aims to provide teachers with a practical guide to the musical content presented in each episode, facilitating its selection and classroom implementation. In this way, it seeks to contribute to a more integrated, meaningful, and motivating approach to music education in the early years of schooling.